HIV serostatus disclosure from partners before sex: results from an online survey of Chinese men who have sex with men. (December 2017) - Tang, Weiming; Cao, Bolin; Liu, Chuncheng; Pan, Stephen; Zhang, Ye; Ong, Jason; Fu, Hongyun; Ma, Baoli; Fu, Rong; Yang, Bin; Ma, Wei; Wei, Chongyi; et al.
Abstract: Background: HIV serostatus disclosure before sex can facilitate serosorting, condom use, and potentially decreased risk of HIV acquisition. However, few studies have evaluated HIV serostatus disclosure from partners before sex. We examined the rate and correlates of receiving HIV serostatus disclosure from regular and casual male partners before sex among an online sample of men who have sex with men (MSM) in China. Methods: An online cross-sectional study was conducted among MSM in eight Chinese cities in July 28–31, 2016. Participants completed questions covering sociodemographic information, sexual behaviours, HIV testing history (including HIV self-testing), self-reported HIV status, and post-test violence (ie, violence after HIV test). Additionally, participants were asked whether they received HIV serostatus disclosure from different kinds of most recent partners before sex. Findings: 2105 men completed the survey. 1809 (86%) were never married, and 746 (35%) had high school or less education. Overall, 1678 (80%) participants reported that they ever had regular male partners, and 1608 (76%) ever had casual male partners. 346 (21%) of 1678 men who ever had regular partners received HIV serostatus disclosure from their most recent regular male partners, while 704 (42%) of 1678 provided HIV status disclosure to their regular partners. Multivariable analysis indicated that participants who ever self-tested for HIV were more likely to have received HIV status disclosure from regular male partners (adjusted odds ratio [aOR] 1·92, 95% CI 1·50–2·44), compared with participants who had never self-tested. Compared with participants who had not received HIV status disclosure from regular partners, men who received disclosure from regular male partners had higher likelihood of experiencing post-test violence (aOR 5·18, 95% CI 1·53–17·58). Similar results were found for receiving HIV serostatus disclosure from casual partners. Interpretation: HIV serostatus disclosure from partners was uncommon among Chinese MSM. Interventions and further implementation research to facilitate safe disclosure are urgently needed. Funding: National Institutes of Health (National Institute of Allergy and Infectious Diseases 1R01AI114310, National Center for Advancing Translational Sciences grant number UL1TR001111)), UNC-South China STD Research Training Centre (Fogarty International Centre 1D43TW009532), UNC Center for AIDS Research (National Institute of Allergy and Infectious Diseases 5P30AI050410), University of California San Francisco Center for AIDS Research (National Institute of Allergy and Infectious Diseases P30 AI027763), and the Bill & Melinda Gates Foundation to the MeSH Consortium (BMGF-OPP1120138).